AB1044 Pain and Psychological Health May Be Associated To Risk Factors for Cardiovascular Disease in Patients with Rheumatic Joint Disease. (15th July 2016) - Provan, S.A.; Berg, I.J.; Dagfinrud, H.; Østerås, N.; Kvien, T.K.; Uhlig, T.
Abstract : Background: Patients with rheumatological joint diseases (RJD) have an increased risk of cardiovascular disease (CVD). There is a lack of knowledge concerning the impact of health status on CVD risk. Augmentation index (AIx) and reactive hyperemia index (RHI) are two markers of CVD risk. High values of AIx, and low values of RHI signify an increased risk of CVD. Objectives: To investigate whether pain and self-reported health status are associated with CVD risk in patients with RJD. Methods: 895 patients with RJD were included. 425 patients with self-reported osteoarthritis (OA), 159 patients with ankylosing spondylitis (AS) and 148 patients with rheumatoid arthritis (RA). Variables of demography, co-morbidities, self-reported pain, health related quality of life (EuroQOL (EQ-5D) (AS and OA)) and health status (Short form 36 (SF-36)) were collected on questionnaires. Clinical examinations were performed by a study nurse and the 28-tender joint count recorded (28-TJC) (RA and OA). AIx (Sphygmocor apparatua (Atcor®)) and RHI (Itamar®) were measured. Cross-sectional linear regression analyses were performed with AIx and RHI as dependent variables in separate models. The associations between pain, health status and CVD risk (AIx and RHI as dependent variables) were examined in cross-sectional models adjusted for type of RJD, age and sex. (AIx was also adjusted for height). Possible confounders were identified from previous literature and plotted in directed acyclic graphs 1 . Relevant variables were entered into multivariate models. Results: 895 patients with RJD were included, mean age was 61.3 (range 28–85), (64.7%) females. AIx was available in 143 patients with RA, 130 with AS, and 424 with OA. RHI was available in 143 patients with RA and 42 with AS. The results from the linear regression models are presented in the table. The multivariate models were adjusted for body mass index and disease activity (DAS ≥2.6 or ASDAS ≥1.3 = active disease). Conclusions: Pain and psychological health are related to markers of CVD risk in RJD, after adjustments for disease activity. These novel findings require confirmation in longitudinal studies. References: Williamson EJ. Respirology 2014. Disclosure of Interest: None declared